Une esthétique de chiffonnier (le photographe itinérant) - Asselin, Olivier (CV Photo, 2000)
Summary Asselin recalls the various modern figures of the walker and the modalities of their aesthetic contemplation. The photographer bears a resemblance to the Baudelairean figure of the flâneur, torn between aestheticization of his marginality and the incontrovertible realities of the world of the marketplace. He is forced, a little like a ragpicker, to recycle the aesthetic values of his images for that marketplace.